Local glucocorticoid synthesis regulates house dust mite-induced airway hypersensitivity in mice - Merk, Verena M.; Phan, Truong San; Wiedmann, Alice; Hardy, Rowan S.; Lavery, Gareth G.; Brunner, Thomas (Frontiers in Immunology, 2023)
Background: Extra-adrenal glucocorticoid (GC) synthesis at epithelial barriers, such as skin and intestine, has been shown to be important in the local regulation of inflammation. However, the role of local GC synthesis in the lung is less well studied. Based on previous studies and the uncontentious efficacy of corticosteroid therapy in asthma patients, we here investigated the role of 11βhydroxysteroid dehydrogenase 1 (11β-HSD1/Hsd11b1)-dependent local GC reactivation in the regulation of allergic airway inflammation. Methods: Airway inflammation in Hsd11b1-deficient and C57BL/6 wild type mice was analyzed after injection of lipopolysaccharide (LPS) and anti-CD3 antibody, and in acute and chronic models of airway hypersensitivity induced by house dust mite (HDM) extract. The role of 11β-HSD1 in normal and inflammatory conditions was assessed by high dimensional flow cytometry, histological staining, RT-qPCR analysis, ex vivo tissue cultures, GC-bioassays and protein detection by ELISA and immunoblotting.Results: Here we show that lung tissue from Hsd11b1-deficient mice synthesized significantly less GC ex vivo compared with wild type animals in response to immune cell stimulation. We further observed a drastically aggravated phenotype in Hsd11b1-deficient mice treated with HDM extract compared to wild type animals. Besides eosinophilic infiltration, Hsd11b1-deficient mice exhibited aggravated neutrophilic infiltration caused by a strong Th17-type immune response.We propose an important role of 11β-HSD1 and local GC in regulating Th17-type rather than Th2-type immune responses in HDM-induced airway hypersensitivity in mice by potentially controlling Toll-like receptor 4 (TLR4) signaling and cytokine/chemokine secretion by airway epithelial cells.